Tectonic geomorphology of the Fortuna Fault and the Venado Transtensive system, northern Costa Rica - Argüello Sáenz, Alejandro (2024)
The northwestern dextral strike-slip Haciendas-Chiripa fault system crosses the backarc region of northern Costa Rica. This system defines the eastern border of the Guanacaste Volcanic Arc Sliver, which is moving northwest at ~ 11 mm year−1 and nearly parallel to the Middle America Trench. The NW-oriented dextral strike-slip Fortuna Fault is a branch within the Haciendas-Chiripa fault system. A right bend along the Fortuna Fault in the Venado region originates the Venado Transtensive Zone. The Venado region is located within a backarc Miocene sedimentary basin, including sandstone, mudstone, and limestone (with karst), covered by Plio-Quaternary volcanic rocks. The Fortuna Fault and the Venado Transtensive Zone were defined using geomorphological and geological evidence. Tectonic landforms typical of strike-slip and normal faulting (e.g., scarps, linear valleys, and displaced drainages) were identified in the study region. The Venado dilatational stepover developed inside a tilted planation surface, causing Pleistocene to Holocene alluvial depocenters to locate in its eastern sector. Our work contributes to a better definition of the Haciendas-Chiripa fault system and its relationship with the tectonic sliver in northern Costa Rica.